Simulation Study on Image Characteristics of Typical GPR Targets in Water Conservancy Projects. (17th March 2021) - Cao, Jie; Yuan, Baoyuan; Bai, Yun
Abstract : With the development of the global economy, the deep leakage of reservoirs is still a serious threat to the foundation construction of key water conservancy projects such as dam foundations and bridges. Ground penetrating radar (GPR) is an effective underground imaging and detection technology. In this paper, the Groundvue series of ground penetrating radars is introduced in Britain using the 948 project fund of the Ministry of Water Resources. It is a radar with the lowest frequency in the world at present, improving detection depths and helping to ensure the reliability of a reservoir dam's foundation. Through a large number of field tests, simulation experiments, FDTD numerical simulations, and practical engineering applications, this paper summarizes the reservoir leakage analysis method based on the Groundvue radar. The successful application at the Nanmenxia Reservoir shows that this method can effectively detect the location and path of reservoir leakage and provide technical support for the design and construction of a reservoir reinforcement project.